A pozitív testkép kialakításának lehetőségei serdülő lányok körében: Julia V. Taylor: The Body Image Workbook for Teens: Activities to Help Girls Develop a Healthy Body Image in an Image-Obsessed World - Obál, Annabella; Tari, Gergely Róbert; Pikó, Bettina (Iskolakultúra, 2023)
Taylor, J. V. (2014). The Body Image Workbook for Teens: Activities to Help Girls Develop a Healthy Body Image in an Image-Obsessed World. Instant Help Books.